Taxation Liability Determination Framework Predicated on Adherence to Taxpayer Obligations - Ismir, Adi; Mutamimah, Mutamimah (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This study aims to develop a tax payment decision model based on taxpayer compliance, specifically examining how tax awareness and understanding of tax regulations influence taxpayers' decisions to pay regional taxes in Batang Hari Regency. Materials and methods: This research employs a quantitative explanatory approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data were collected through structured questionnaires from 135 active regional taxpayers across eight tax sectors (PBB-P2, PBJT, Advertisement, etc.) using total sampling technique. The study examined the relationships between tax regulation (X1), taxpayer awareness (X2), taxpayer compliance (Z as mediating variable), and tax payment decisions (Y). Results: All research hypotheses were statistically significant. Tax regulation and taxpayer awareness positively influence taxpayer compliance (path coefficients: 0.403 and 0.568 respectively). However, tax regulation shows a negative direct effect on tax payment decisions (-0.223), while taxpayer awareness demonstrates a positive direct effect (0.207). Taxpayer compliance significantly mediates the relationship between both independent variables and tax payment decisions (0.469). The model explains 59% of taxpayer compliance variance and 39.2% of tax payment decision variance. Conclusions: Taxpayer awareness and tax regulations significantly influence taxpayer compliance, which subsequently affects actual tax payment decisions. High levels of awareness, supported by clear, fair, and easily understood regulations, effectively increase compliance rates and encourage voluntary tax payments. Taxpayer compliance plays an essential mediating role in strengthening the relationship between regulations and awareness toward tax payment decisions.